Binio Formation Characterisation Using Seismic Acoustic Impedance Inversion in the Lotus Field of the Central Sumatra Basin - Ni Putu Juliyant Ananda Rika Pangastuti; Mohammad Syamsu Rosid; Edy Wijanarko (Scientific Contributions Oil and Gas, 2025)
The Binio Formation, the target of this study, is located in the Lotus Field, Central Sumatra Basin. P-impedance parameters from acoustic impedance (AI) inversion analysis are used to identify rock lithology and fluid content. Petrophysical analysis was conducted on three wells using well log data to determine reservoir characteristics and identify prospect zones. The reservoir in the Binio Formation is a sandstone that is considered favourable for hydrocarbon accumulation. This study determines lithology, fluid content and reservoir structure. Sensitivity analysis showed that the porosity log parameter is sensitive to lithological separation. A potential hydrocarbon area was detected using seismic methods. Model-based inversion methods showed that the AI values of the sandstone reservoir ranged from 9,670 to 27,070 (ft/s)(gr/cc). The geological structure in the Lotus Field is generally quite complex, consisting of an anticline structure and a normal fault. Following conversion to porosity, the effective porosity value for the P1 reservoir was 0.4 (fraction). The root mean square attribute results showed the presence of bright spots, and the reservoir was clearly detected within the 10 ms analysis window. The prospect zone in the P1 well lies at a depth of 2,400–2,800 ft, with interpretation indicating that the fluid content is gas.